(3NeSjfjI GdYWGA GdeJhGUd(B.... (3hehGVjY GNQi (B/s - (3jYjT, eMeO QDhas; (3SdjeGfs ((3JhfS (B:s (3EJMGO EPGYGJ GdOhd GdYQHjI ,s, 2020)
(3dbO GJGMJ aYGdjI gPg GdfOhI GdfXQ aj YOI eMGhQ GJUdJ HhGbY bjGSGJ LeghQ GdGPGYI h GdJdaRjhf aj GdhWf GdYQHj Je GdJYQa Gdi efGgL h GdJLgjRGJ GdeJHY aj GdbjGS GVGaI Gdi YQV JLGQH aj HYV GdOhd GdYQHjI h cPdc GdGJLGgGJ GdMOjKI aj bjGSGJ LeghQ GdGPGYI h GdJdaRjhf ef NdGd GdGWdGY Ydi GdJLQHI GdhQHjI s
Keywords: (3GdEPGYIs; (3GdEYdGe GdSeYj GdHUQjs; (3GdJdaRjhfs; (3GdejOjG h GdJdaRjhfs